Spatio‐temporal variability of cloud cover types in West Africa with satellite‐based and reanalysis data. (14th October 2019) - Danso, Derrick Kwadwo; Anquetin, Sandrine; Diedhiou, Arona; Lavaysse, Christophe; Kobea, Arsène; Touré, N'Datchoh Evelyne
Abstract: This study aims to understand and document the occurrence and variability of cloud cover types in West Africa (WA). Investigations are carried out with a 10‐year hourly record of two cloud data products: CERES passive satellite observations and ERA5 reanalysis. The seasonal evolutions of high (HCC), middle (MCC), low (LCC) and total (TCC) cloud cover are examined. Both products agree on the seasonal and spatial occurrence of cloud cover, although CERES presents lower values of cloud fraction than ERA5 which is partly attributed to the inability of the satellite sensor to detect optically thin clouds in the atmosphere. Southern WA is found to be cloudier than other parts of the region in all seasons with mean TCC fractions of 70 and 80% for CERES and ERA5 respectively during the monsoon season. In all seasons, the presence of LCC over large areas of the Sahel/Sahara region is noted in the CERES product. This could be due to a possible misinterpretation of Saharan dust as low clouds which may have thus, caused it to overestimate the occurrences and fractions of LCC over this region. Northern WA is associated with higher frequencies of no cloud occurrence events, unlike the south where cloudless skies are rarely observed. Furthermore, in southern WA, overcast conditions of LCC are observed for a significant number of times (up to 20% of the time during the rainy season in CERES and 40% in ERA5). The climatology of cloud cover presented in this study could be useful for the planning of solar energy projects. Abstract : The variability and occurrence of three different cloud types (high‐level, mid‐level and low‐level cloud types), are investigated in West Africa with CERES satellite‐based and ERA5 reanalysis data. To a large extent, both datasets agree on the seasonal and spatial evolutions of different cloud types. However, the climatology of variability and occurrence frequencies of different cloud types reveal some important differences between the two products and are linked to satellite retrieval algorithm or the model convective parametrization and microphysical scheme.